The oxidative stress and antioxidant status at children with immune thrombocytopenic purpura: Endothelial nitric oxide synthase Glu298Asp gene polymorphism - Arslan, F.; Akarsu, S.; Erol, D.; Kara, M. (Wiley-Blackwell, 2012)
[Abstract Not Available]